The Production and Distribution Systems of the Shea Crop in Northern Ghana: A Mixed-Methods Analysis of Value Chains and Sustainability - Abdul Kadir Adam; Himadri Barman (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2026)
This paper analyzes the shea value chain of Northern Ghana, from harvesting to marketing, and identifies its inefficiencies, key challenges, and socio-economic dynamics. The study adopts a mixed-methods approach, combining quantitative data from 402 value chain actors across four districts (Tolon/Kumbungu, Fumbisi, Savelugu/Nanton, and Sagnarigu) with a literature review. Variables such as landholding size, yield, education level, harvesting practices, production costs, and distribution satisfaction were analyzed using descriptive statistics, chi-square tests, Fisher’s exact test, Pearson correlation, linear regression, and ANOVA. The shea value chain is predominantly female-driven (94.8%) and heavily reliant on manual labor, with limited value addition and low market penetration. Key issues include small landholdings (67.4% ranging from 4–6 hectares), sustainability pressures (69.7% reporting a lack of shea trees), a strong reliance on local markets (78.4%), and high levels of dissatisfaction (68.9%). Significant relationships were found between landholding size and yield (Fisher’s exact test = 54.783, p < 0.001), production costs and landholding size (ANOVA F = 3.915, p = 0.004), and yield and harvesting practices (F = 2.961, p = 0.032). Major constraints include insecure land tenure (71.9%), equipment shortages (42.0%), and limited access to inputs (38.1%). Policy recommendations include land reform, increased investment in infrastructure, strengthening cooperatives, and developing gender-responsive programs